Antigenic fingerprinting of diphtheria toxoid adsorbed to aluminium phosphate. (May 2017) - Westdijk, Janny; Metz, Bernard; Spruit, Nanda; Tilstra, Wichard; van der Gun, Johan; Hendriksen, Coenraad; Kersten, Gideon
Abstract: The antigenicity of alum-adsorbed diphtheria toxoid (DTd) was determined in combination vaccines, containing DTd, tetanus toxoid and inactivated poliovirus. A panel of monoclonal antibodies was used, covering five epitopes, distributed over the antigen. The resulting antigenic fingerprint of DTd demonstrates consistency of adsorption at antigen level in final product combination vaccines. The antigenic quality of DTd alone, adsorbed to aluminium phosphate, was also determined and compared with pre-adsorbed toxoid (starting material as well as toxoid desorbed from aluminium phosphate). Some epitopes became less accessible after adsorption, while others became relatively better exposed. Some epitopes disappeared almost completely upon adsorption, but were re-established after desorption of the antigen. The results indicate that DTd is adsorbed to aluminium phosphate in a preferred orientation and not randomly.